2018
DOI: 10.1016/j.idc.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Illnesses in Children and Adolescents

Abstract: Norovirus is a leading cause of childhood vomiting and diarrhea in the United States and globally. Although most illnesses caused by norovirus are self-resolving, severe outcomes may occur from dehydration, including hospitalization and death. A vast majority of deaths from norovirus occur in developing countries. Immunocompromised children are at risk for more severe outcomes. Treatment of norovirus illness is focused on early correction of dehydration and maintenance of fluid status and nutrition. Hand hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 89 publications
(96 reference statements)
2
47
0
1
Order By: Relevance
“…The prevalence was more or less similar to previous studies [16,17]. This finding supports the hypothesis that norovirus is a wide-spread virus that affects both young children and adolescents in developing countries [18]. The predominant genotype was GII detected in 80.97%.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence was more or less similar to previous studies [16,17]. This finding supports the hypothesis that norovirus is a wide-spread virus that affects both young children and adolescents in developing countries [18]. The predominant genotype was GII detected in 80.97%.…”
Section: Discussionsupporting
confidence: 90%
“…Norovirus is responsible for 20 million illnesses annually in the United States, including approximately 2 million outpatient visits, and is a leading cause of acute gastroenteritis (AGE) across all age groups [1]. The burden of disease is substantial; children <5 years of age have the highest rates of norovirus-associated medical visits [2], while older adults are at greatest risk for norovirus-associated deaths [3,4]. Several candidate vaccines are currently in clinical trials, including an oral tablet vaccine that recently reported phase I results from a bivalent GI.1/GII.4 formulation in adults, as well as a bivalent GI.1/GII.4 consensus sequence virus-like particle intramuscular vaccine candidate that has conducted phase II trials in children, adults, and the elderly [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Norovirus (Norovirus), a member of the Caliciviridae family, is a highly contagious virus with a low infection dose of approximately 20 virus particles [1][2][3]. Norovirus can be divided into 10 genogroups [4], and GII, GI and GIV can cause human infection [5].…”
Section: Introductionmentioning
confidence: 99%